Correlates of uptake of COVID-19 vaccines and motivation to vaccinate among Malawian adults - Hannah S. Whitehead; John Songo; Khumbo Phiri; Pericles Kalande; Eric Lungu; Sam Phiri; Joep J. van Oosterhout; Risa M. Hoffman; Corrina Moucheraud (Taylor & Francis Group, 2023)
COVID-19 vaccine coverage in most countries in Africa remains low. Determinants of uptake need to be better understood to improve vaccination campaigns. Few studies from Africa have identified correlates of COVID-19 vaccination in the general population. We surveyed adults at 32 healthcare facilities across Malawi, purposively sampled to ensure balanced representation of adults with and without HIV. The survey, informed by the World Health Organization's Behavioural and Social Drivers of Vaccination Framework, asked about people's thoughts and feelings about the vaccine, social processes, motivation to vaccinate, and access issues. We classified respondents' COVID-19 vaccination status and willingness to vaccinate, and used multivariable logistic regression to assess correlates of these. Among 837 surveyed individuals (median age was 39 years (IQR 30-49) and 56% were female), 33% were up-to-date on COVID-19 vaccination, 61% were unvaccinated, and 6% were overdue for a second dose. Those up-to-date were more likely to know someone who had died from COVID-19, feel the vaccine is important and safe, and perceive pro-vaccination social norms. Despite prevalent concerns about vaccine side effects, 54% of unvaccinated respondents were willing to vaccinate. Access issues were reported by 28% of unvaccinated but willing respondents. Up-to-date COVID-19 vaccination status was associated with positive attitudes about the vaccine and with perceiving pro-vaccination social norms. Over half of unvaccinated respondents were willing to get vaccinated. Disseminating vaccine safety messages from trusted sources and ensuring local vaccine availability may ultimately increase vaccine uptake.